Thyroid hormone receptor- and stage-dependent transcriptome changes affect the initial period of Xenopus tropicalis tail regeneration - Shouhong Wang; Liezhen Fu; Bin Wang; Yanmei Cai; Jianping Jiang; Yun-Bo Shi (BMC Genomics)
Abstract Background Thyroid hormone (T3) has an inhibitory effect on tissue/organ regeneration. It is still elusive how T3 regulates this process. It is well established that the developmental effects of T3 are primarily mediated through transcriptional regulation by thyroid hormone receptors (TRs). Here we have taken advantage of mutant tadpoles lacking both TRα and TRβ (TRDKO), the only receptor genes in vertebrates, for RNA-seq analyses to investigate the transcriptome changes underlying the initiation of tail regeneration, i.e., wound healing and blastema formation, because this crucial initial step determines the extent of the functional regeneration in the later phase of tissue regrowth. Results We discovered that GO (gene ontology) terms related to inflammatory response, metabolic process, cell apoptosis, and epithelial cell migration were highly enriched among commonly regulated genes during wound healing at either stage 56 or 61 or with either wild type (WT) or TRDKO tadpoles, consistent with the morphological changes associated with wound healing occurring in both regenerative (WT stage 56, TRDKO stage 56, TRDKO stage 61) and nonregenerative (WT stage 61) animals. Interestingly, ECM-receptor interaction and cytokine-cytokine receptor interaction, which are essential for blastema formation and regeneration, were significantly enriched among regulated genes in the 3 regenerative groups but not the non-regenerative group at the blastema formation period. In addition, the regulated genes specific to the nonregenerative group were highly enriched with genes involved in cellular senescence. Finally, T3 treatment at stage 56, while not inducing any measurable tail resorption, inhibited tail regeneration in the wild type but not TRDKO tadpoles. Conclusions Our study suggests that TR-mediated, T3-induced gene regulation changed the permissive environment during the initial period of regeneration and affected the subsequent patterning/outgrowth period of the regeneration process. Specifically, T3 signaling via TRs inhibits the expression of ECM-related genes while promoting the expression of inflammation-related genes during the blastema formation period. Interestingly, our findings indicate that amputation-induced changes in DNA replication-related pathways can occur during this nonregenerative period. Further studies, particularly on the regenerative microenvironment that may depend on ECM-receptor interaction and cytokine-cytokine receptor interaction, should provide important insights on the regulation of regenerative capacity during vertebrate development.